Influence of gatorade ingestion by athletes on sanguine glucose behavior cardiac frequency - João Carlos Bouzas Martins (Journal of Physical Education (Maringá), 2008)
The aim of this study was to evaluate the effetcts of the commercial hydrator Gatorade ingestion on sanguine glucemia and on the cardiac frequency while male athletes were performing an eminently aerobic activity. Twenty cyclist were evaluated (n = 9), runners (n = 5), swimmers (n = 5) and athletes who practised triathlo (n = 1). The athletes were evaluated to determine max. VO2. After the results came up, each athlete was submitted to a physical exercise under max. VO2 of 70% in an eletromagnectic cicloergometre (FUNBEC), for a period of two hours in the maximum, in two different situations, with an interval of seven days. In the first situation the subject drank water to hydrate, and in the second, the commercial hydrator Gatorade was used. The hydration with Gatorade produced a significant difference, not only for the sanguine glucemia (p= 0,0001) but for cardiac frequency as well which was considerably reduced (physical+0,00003). The use of Gatorade presented advantages compares to hydratation with Gatorade produced a significant difertence, not only for the sanguine glucemia (p = 0,0001) but for cardiac fequency as well which was considerably reduced (p +0,00003). The use of Gatorade presented advantages compares to hydration with water, because it was possible to maintain and increase an ideal state of sanguine glucemia for exercise, in addition to causting less cardiovascular "stress".